Intensitas Penggunaan Media Android Hubungannya dengan Minat Belajar Peserta Didik - Abdurrohman, Abdurrohman; Hasbullah, Hasbullah; Juhji, Juhji (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
This study aims to examine whether there is a relationship between the intensity of the use of Android media with the learning interest of students in Islamic Religious Education subjects. The study was conducted at State High School 3 Serang City, Banten Province. The research method uses correlational analysis. The study sample was taken as many as 40 (forty) students who are still actively learning in the current school year. Research data were collected through a validated questionnaire. The data were analyzed using Pearson's correlation techniques through the help of the SPSS version 16.00 application. The results showed a weak positive relationship between the intensity of the use of Android media with the interest in learning of students in Islamic Religious Education subjects. Thus, students' interest in learning is largely influenced by other factors outside the variables of this study.